EU Enlargement and Satisfaction with Democracy: A Peculiar Case of Immizerising Growth - Barbara Dluhosch; Daniel Horgos; Klaus W. Zimmermann (FIW - Research Centre International Economics, 2013)
Studies on EU enlargement mostly focus on its welfare-economic and much less so on its public-choice dimension. Yet, the latter may be as important as the former when it comes to sustain integration. This paper aims at filling the gap by exploring theoretically and empirically how enlargement of multi-level systems like the EU affects satisfaction with democracy (SWD) and voter turnout (PART). In order to assess the effects of a widening in membership, we present a novel approach that draws on the probability of being outvoted. We find that, given the institutional arrangement, enlargement tends to depress SWD. Our theoretical results are backed by empirical evidence in German Eurobarometer data displaying a tendency towards a decline in SWD that shows up in a significant fall in PART with growth in EU-membership.
Keywords: F55; D72; H77; 330; European Union; Enlargement; Multi-level Systems; Democracy; Regime Satisfaction